Penerapan Pembagian Bagian Suami dan Isteri Pasal 179 dan 180 Kompilasi Hukum Islam (KHI) - Syuhada' Syuhada' (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2018)
The Qur’an describes the heirs only three verses that govern in detail, detail, and clear. Article 179 KHI husband gets half the part on the condition that the corpse does not leave the child or grandchildren and gets a quarter of the portion on the condition that the corpse leaves the child or grandchild. The widow or widow (wives) in section 180 KHI gets a fourth part on the condition that the corpse leaves no children or grandchildren and gets an eighth part on the condition that the corpse leaves the child or grandchild. Partial, quarter, and eighth part of section 179 and section 180 KHI are from inheritance or inheritance. Surely the property is not a property that is still a treasure of gono gini or mutual property. So if the property is still belonging together then it should be divided into two parts if each husband is working together, the husband works outside the house while the wife works in the house or divided three two parts for the husband and one part for the wife or vice versa.